2012
DOI: 10.1177/0883073812447683
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Retinal Nerve Fiber Layer Thickness and Macular Volume in Pediatric Multiple Sclerosis

Abstract: Retinal atrophy is well known in adult-onset multiple sclerosis but remains unexplored in children. We aimed to determine retinal nerve fiber layer thickness and macular volume in pediatric patients, with and without optic neuritis and their relations with visual evoked potentials. We also examined macular volume changes at month 12. Retinal nerve fiber layer thickness of all quadrants and macular volume were measured in 28 relapsing remitting multiple sclerosis eyes and 30 control eyes using optical coherence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 32 publications
(47 reference statements)
1
13
0
Order By: Relevance
“…2 Also in line with our findings, another study of 14 pediatric patients with MS reported no difference in VEP latencies between MS-ON eyes and MS non-ON eyes ( p = 0.524) or between MS-ON eyes and MS fellow eyes ( p = 0.654). 5 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Also in line with our findings, another study of 14 pediatric patients with MS reported no difference in VEP latencies between MS-ON eyes and MS non-ON eyes ( p = 0.524) or between MS-ON eyes and MS fellow eyes ( p = 0.654). 5 …”
Section: Discussionmentioning
confidence: 99%
“…3 In adults with MS, thinning of the retina has also been documented in the absence of ON, although thinning in non-ON eyes in pediatric MS has been variably detected. 46 In pediatric-onset MS, the likelihood of an OCT or VEP abnormality in MS eyes, with or without ON, has not been calculated. We sought to compare OCT and pVEPs in a cohort of pediatric-onset MS participants, with and without a history of ON, in order to inform on the relative utility of these tests in the pediatric context.…”
mentioning
confidence: 99%
“…While decreased lowcontrast letter acuity scores and retinal nerve fiber layer (RNFL) thinning have been demonstrated in pediatric patients with MS with a history of ON, 33 there are conflicting data regarding the relationship between deficits in low-contrast visual function and retinal pathology in the eyes of children with MS unaffected by a clinical attack of ON (MS non-ON eyes). 34,35 One study has shown preserved RNFL in MS non-ON eyes, 33 suggesting that OCT may capture only local thinning after ON. However, 2 other studies have shown decreased RNFL in pediatric MS non-ON eyes, suggesting that OCT might capture a more global degenerative component of MS. 34,35 Further validation of OCT as an outcome in pediatric MS is needed.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…34,35 One study has shown preserved RNFL in MS non-ON eyes, 33 suggesting that OCT may capture only local thinning after ON. However, 2 other studies have shown decreased RNFL in pediatric MS non-ON eyes, suggesting that OCT might capture a more global degenerative component of MS. 34,35 Further validation of OCT as an outcome in pediatric MS is needed.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…In pediatric MS, eyes with a history of ON have been reported to have 10%-20% thinner RNFL than MS non-ON eyes or control eyes and 6% lower macular volumes. [20][21][22] Using time-domain OCT, severe RNFL thinning may occur after a single episode of ON in certain cases, including ON associated with transverse myelitis and ADEM (67 microns) vs MS (83 microns) and healthy age-and sex-matched controls (107 6 12 microns), suggesting potentially different pathophysiologic processes driving these entities. 22 In recurrent disease in children, stepwise decrease in RNFL (8-10 microns) may be seen following each episode of ON.…”
mentioning
confidence: 99%